Determinan Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening pada Perusahaan Sub Sektor Makanan dan Minuman - Selfi Nur’aisyah; Siti Ruhana Dara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to analyze the effect of capital structure, liquidity, and activity on firm value with profitability as an intervening variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses secondary data. The sampling technique in this research is purposive sampling. There are 15 out of 30 companies that meet the criteria. This test uses Eviews 10. The data analysis method is carried out with multiple linear regression and uses path analysis for profitability as an intervening variable. The results showed that capital structure, liquidity, and activity had no effect on profitability. Capital structure and activity affect firm value, while liquidity and profitability have no effect on firm value. Capital structure, liquidity, and activity have no effect on firm value through profitability